Laparoscopic portosystemic shunt attenuation in two cats. Issue 1 (March 2022) - Izzo, Francesca; Poggi, Edoardo; Pérez Duarte, Francisco J; Cinti, Filippo
Case series summary: Gradual attenuation of an extrahepatic portosystemic shunt using cellophane banding was achieved with a laparoscopic technique in two cats. The portosystemic shunts were treated via a right or left lateral laparoscopic approach. Ultrasonography or CT angiography were used to verify the results of surgery. The success of the procedure was confirmed by normalisation of serum bile acid concentrations and clinical signs at the final re-evaluation. Relevance and novel information: The aim of this case series was to determine the feasibility and outcome of laparoscopy for portosystemic shunt attenuation in two cats. Laparoscopic portosystemic shunt attenuation appeared to be a feasible, safe and effective procedure in cats.